Intellectual capital contribution to organizational performance in Malaysian banking and non-banking sectors - Hashim, Maryam Jameelah; Othman, Idris; Syed Jaafar Alhabshi, Syed Musa (American Scientific Publishers, 2017)
The endurance and achievement of a firm mostly rely on the strategic management of its intellectual capital besides financial resources. Nevertheless, there exist a few disputes in managing intellectual capital, which is the managers are not concern with the valuable resources acquired by their firms would lead to new strategies accomplishment. The components of intellectual capital that will be discussed in this paper are human capital, structural capital, customer capital and social capital. The aim of this study is to empirically investigate the association between four components of intellectual capital and organizational performance of banking and non-banking sectors in Malaysia. This research was conducted on private organizations in two states namely Selangor and Wilayah Persekutuan in West Malaysia. Structured questionnaires using five-point Likert scale were administrated and distributed to 400 respondents selected randomly based on the non-probability convenience sampling method. A total of 302 employees participated in this study to examine the association of intellectual capital components towards the organizational performance of banking and non-banking sector in West Malaysia. Pearson Correlation, Cronbach’s alpha and Multiple Regressions were employed to analyze the association between components of intellectual capital and organizational performance. The contribution of this study is obvious as the resulting outcomes can be capitalized as guidelines to entrepreneurs, executives, managers and policy makers in managing intellectual capital within the Malaysian banking and non-banking industry context. The results revealed that intellectual capital as a whole has a significant relationship with the performance of banking and non-banking sectors in Malaysia.